Effect of Chitosan concentration on antifouling performance of thin film composite / Norin Zamiah Kassim Shaari, Nadia Fathiah Mohd Dandan and Nurul Aida Sulaiman - Kassim Shaari, Norin Zamiah; Mohd Dandan, Nadia Fathiah; Sulaiman, Nurul Aida (Universiti Teknologi MARA Shah Alam, 2019)
Wastewater treatment is an approach to make sure the water supply is clean and free from unwanted particles. Membrane technology is one of the methods applied to the treatment process. This study describes the production of thin film composite (TFC) membrane, which was formulated from polysulfone as a porous support membrane, and hybrid membrane as a barrier layer. The hybrid membrane was formulated from a blend of chitosan, polyethylene glycol (PEG) and tetraethylorthosilicate (TEOS). The objective of this study is to investigate the effects of varying chitosan concentrations (1, 2 and 3 wt.%) on the properties of the thin-film composite membrane in terms of thermal, pure water flux and antifouling properties. It was found that the membrane with 2 wt.% chitosan yields the highest water flux and good antifouling property. The findings of this study are very significant as it provides a wide knowledge of separation performance of thin film composite (TFC) membrane.